Treatment with soy isoflavones during early adulthood improves metabolism in early postnatally overfed rats. (2nd January 2018) - Silva, Pamelli; Ribeiro, Tatiane Aparecida; Tófolo, Laize Peron; Prates, Kelly Valério; Francisco, Flávio Andrade; Silveira, Sandra da Silva; Malta, Ananda; Lopes, Denise Alves; Miranda, Rosiane Aparecida; Palma-Rigo, Kesia; Torrezan, Rosana; Mathias, Paulo Cezar de Freitas
Abstract : Purpose : The incidences of obesity and related diseases have reached epidemic proportions, and new therapeutic approaches are needed. Soy isoflavones have been identified as an important dietary factor for preventing and treating metabolic dysfunction. This study examined the effects of high doses of isoflavone on glucose and fat metabolism in a model of programmed obesity and evaluated its effects on the autonomic nervous system. Methods : Litters of Wistar rats were standardized at nine pups per dam in normal litters (NL) or reduced to three pups per dam at the third day of life (P3) in small litters (SL) to induce postnatal overfeeding. Gavage with a soy bean isoflavone mixture (1 g/day) diluted in water was started at P60 and continued for 30 days. The control animals received vehicle gavage. At P90, biometric and metabolic parameters as well as direct autonomic nerve activity were measured. Results : Increases in glycaemia and insulinaemia observed in SL rats were reduced by isoflavone treatment, which also caused lower glucose-induced insulin secretion by pancreatic islets. Sympathetic activity in the major splanchnic nerve was increased, while vagus nerve activity was reduced by isoflavone treatment. The dyslipidaemia induced by overfeeding in SL rats was restored by isoflavone treatment. Conclusion : The present study shows that treatment with isoflavone reduces adiposity and improves glucose and lipid metabolism. Collectively, these effects may depend on autonomic changes.